Ole luonto:Luontoyhteyden vahvistaminen taide museopedagogian avulla - Jokela, Timo; Huhmarniemi, Maria; Mäkitalo, Tanja (Intellect, 2024)
This chapter presents the implementation and outcomes of a developing pedagogical art workshop for the art exhibition With the Last Wolf in the Särestöniemi Museum in Kittilä in Northern Finland. According to Mayer (2005), art history has played a determining role in the content of educational experiences in art museums, and to learn how to teach, art museum educators have looked to sources beyond art history and that is why art history has played a determining role in the content of educational experiences in art museums. I. In this chapter, we move from museum pedagogy derived from discipline-centred art history to transformative experiences for visitors and co-knowing-centred pedagogy in a post-humanistic sense. We concentrate on the test bed in the Särestöniemi Museum to answer the research question: How can art museum pedagogy enhance nature connectedness? We also ponder the potential of new kinds of art education entrepreneurship related to the Northern ecoculture due to the growing interest in the creative economy in the Arctic (Jokela et al., in press) and in creative tourism (Huhmarniemi et al., 2021; Kugapi, 2020).